RELATIONSHIP OF LUNAR PHASES TO CRIMES COMMITTED IN ZAMBOANGA DEL NORTE - Velasco, Jonnel D.; Pallega, Rowell B.; Daymiel, Rheychold J. (Future Science / FSH-PH Publications, 2021)
Human behavior appeared to be influenced by lunar phase. Crimes still committed despite the government efforts to prevent and suppress it. Some authors claimed that the moon of the solar system affect the human body and the planet earth. The term lunacy derived from the idea that the lunar cycles affect human behavior and it is a widely believed phenomenon that a full moon can increase criminal behavior. This study aimed to determine the relationship between lunar phases and crimes committed in the two cities of Dipolog and Dapitan. Documentary analysis and unstructured interviews were conducted to gather information. The data were taken from the reported crimes in the two police stations. Statistical tools used were frequency count and chi-square test of both difference and relationships respectively. The most common index crimes were theft, physical injury and threat. Whereas, non-index crimes were malicious mischief and violations to RA 7610 and RA 9262. Results revealed that most of the index crimes happened during the first quarter and during new moon phase. Non-index crimes on the other hand, happened at any lunar phase. The occurrence of index and non-index crimes are likely to be influenced by the lunar phases. Philippine National Police might set-up additional preventive measures to prevent would be criminals from committing theft, physical injury and threat. Police presence be increased more during first quarter and new moon phases to prevent occurrence of crime as well as implement intensive community policing program to protect the community from untoward crime incidence.